Production of haploid wheat plants from wheat (Triticum aestivum L.) x maize (Zea mays L.) cross system - Niroula, Raj K; Bimb, Hari P; Thapa, Dhruva B; Sah, Bindeswor P; Nayak, Sanothos (Himalayan Journal of Sciences, 2008)
The present study was carried out taking single F1 wheat and four maize varieties, viz. Arun-1, Arun-2, Khumal Yellow and Rampur Composite, to determine the efficiency and influence of maize genotypes on various parameters of haploid formation. Wheat spikelets were hand pollinated with freshly collected maize pollen, and 1 ml of 100 ppm 2,4-D was immediately injected on the uppermost internode. Twenty-four hours after 2,4- D injection, the cups of the florets were filled with the same solution of 2,4-D for two more consecutive days. Seventeen days after pollination, the embryos were excised and cultured in half-strength MS basal medium supplemented with 30 g/l sucrose, and 7 g/l agar. The cultured embryos were maintained at 25°C with 16/8 hours light/darkness after treating in the dark for seven days at 4°C and incubation in the dark for seven days at 25°C. Application of 2,4-D after pollination was found to be essential to the recovery of culturable size of embryos. The significant effect of maize genotypes on frequency of ovary development, embryo formation and haploid plant per pollinated floret was observed. The mean percentages of embryo formation and haploid plants per pollinated floret varied from 5.17 to 21.45 and 0.96 to 10.15, respectively, depending upon the maize varieties used. The highest frequency of embryo recovery and plant per floret was found when wheat F1 was pollinated with Arun-2 followed by Arun-1 and Khumal Yellow. It is suggested that the production of dihaploids (DHs) in wheat can be enhanced by using more responsive maize genotypes as pollinators. Key words: 2,4-D, caryopsis, floret, haploid embryo, wheat x maize cross Himalayan Journal of Sciences Vol.4(6) 2007 p.65-69